2022
DOI: 10.3390/biomedicines10102476
|View full text |Cite
|
Sign up to set email alerts
|

Neuron Protection by EDTA May Explain the Successful Outcomes of Toxic Metal Chelation Therapy in Neurodegenerative Diseases

Abstract: Many mechanisms have been related to the etiopathogenesis of neurodegenerative diseases (NDs) such as multiple sclerosis, amyotrophic lateral sclerosis, Parkinson’s disease, and Alzheimer’s disease. In this context, the detrimental role of environmental agents has also been highlighted. Studies focused on the role of toxic metals in the pathogenesis of ND demonstrate the efficacy of treatment with the chelating agent calcium disodium ethylenediaminetetraacetic acid (EDTA) in eliminating toxic metal burden in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 83 publications
1
6
0
Order By: Relevance
“…Two MS subjects discontinued their study participation. The chelation tests showed that all MS patients had high toxic metals levels, and, as previously reported, these levels significantly decreased when measured at the end of treatment [47].…”
Section: Resultssupporting
confidence: 85%
“…Two MS subjects discontinued their study participation. The chelation tests showed that all MS patients had high toxic metals levels, and, as previously reported, these levels significantly decreased when measured at the end of treatment [47].…”
Section: Resultssupporting
confidence: 85%
“…In a previous study conducted by our group [12], we demonstrated decreased blood concentrations of beryllium, copper, chromium, cobalt, nickel, magnesium, and iron, along with an increased lead concentration in pwMS. In addition, the role of metals as risk factors in the etiopathogenesis of neurodegenerative diseases is now recognized, as well as their potential involvement to cause neuronal damage in MS [31]. Thus, it is plausible to propose that the imbalance in blood concentrations of metallic nanoparticles may serve as a biomarker in MS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the bloodbrain barrier controls the transport of metal elements into the brain [34], which is regulated by the homeostasis of metals, especially zinc [35]. Specifically, metal ions interact with specific receptors in the endothelial lining, such as DMT1 and zinc transporters (ZIP8 and ZIP10), to cross the barrier and directly interact with cellular components in the CNS [31]. This interaction can lead to mitochondrial imbalance and increased production of reactive oxygen species, contributing to oxidative stress [31].…”
Section: Discussionmentioning
confidence: 99%
“…Except for the disruptive effect of metals, it was shown that zinc (Zn) may have beneficial effect by blocing the action of cadmium, thus preventing ZO-1 downregulation and dislocation (Branca et al 2022 ). Interestingly, barrier disarrangement by heavy metals could be treated with chelation therapies (Ferrero 2022 ).…”
Section: Bbb Under Neurotoxic Conditionmentioning
confidence: 99%